Concordance of weight status between mothers and children: a secondary analysis of the Pakistan Demographic and health survey VII - Faiz Alam; Mohammed K. Ali; Shivani A. Patel; Romaina Iqbal (BMC, 2024)
Abstract Background Familial concordance of weight status is an emerging field of study that may guide the development of interventions that operate beyond the individual and within the family context. There is a dearth of published data for concordance of weight status within Pakistani households. Methods We assessed the associations between weight status of mothers and their children in a nationally representative sample of households in Pakistan using Demographic and Health Survey data from 2017-18. Our analysis included 3465 mother-child dyads, restricting to children under-five years of age with body mass index (BMI) information on their mothers. We used linear regression models to assess the associations between maternal BMI category (underweight, normal weight, overweight, obese) and child's weight-for-height z-score (WHZ), accounting for socio-demographic characteristics of mothers and children. We assessed these relationships in all children under-five and also stratified by age of children (younger than 2 years and 2 to 5 years). Results In all children under-five and in children 2 to 5 years, maternal BMI was positively associated with child's WHZ. For all children under-five, children of normal weight, overweight, and obese women had WHZ scores that were 0.21 [95% CI (confidence interval): 0.04, 0.37], 0.43 [95% CI: 0.25, 0.62], and 0.51 [95% CI: 0.30, 0.71] units higher than children of underweight women, respectively. For children ages 2 to 5, children of normal weight, overweight, and obese women had WHZ scores that were 0.26 [95% CI: 0.08, 0.44), 0.50 [95% CI: 0.30, 0.71), and 0.61 [95% CI: 0.37, 0.84] units higher than children of underweight women, respectively. There was no association between maternal BMI and child WHZ for children under-two. Conclusions The findings indicate that the weight status of mother's is positively associated with that of their children, particularly after age 2. These associations further strengthen the call for research regarding interventions and policies aimed at healthy weight promotion among mothers and their children collectively, rather than focusing on individuals in isolation.